1001 WAYS TO REWARD EMPLOYEES - Nelson, Bob (Workman Pub. New YorkUS, 1994)
Bases material on the premise that recognition for a job well done is the top motivator of employee performance. Presents 1001 suggestions for managers who wish to recognize significant achievements of employees. Deals with formal and informal rewards and recognition and provides guidelines for effectiviely rewarding and recognizing employees.